Utilization of ICT-Based Learning Media in Islamic Religious Education at SMK Kesehatan Daarul Hidayah Sukoharjo - Sudarto; Mujiburrohman (At Turots: Jurnal Pendidikan Islam, 2026)
The integration of information and communication technology (ICT) in education has become indispensable, including in Islamic Religious Education (PAI). This study explores how ICT-based learning media are utilized in PAI at SMK Kesehatan Daarul Hidayah Sukoharjo, a health vocational high school in Indonesia. Adopting a qualitative descriptive approach, data were collected through interviews with the Principal, Islamic Studies teachers, students, and parents, as well as observations of classroom practices and relevant documents. The results indicate that the use of various ICT-based media—such as digital presentations, educational videos, Qur’an and tajwid applications, online learning platforms (e.g. Google Classroom and WhatsApp), interactive quizzes (Kahoot and Quizizz), online Islamic resources, and video recording of religious practices—has made PAI learning more engaging, interactive, and accessible. These tools enhanced students’ motivation, participation, and understanding of Islamic concepts. The study also identifies challenges like limited infrastructure and varying digital literacy among teachers and students. Overall, the findings affirm that ICT integration in PAI can modernize teaching methods and contextually instill Islamic values in the digital era. Continuous support in teacher training and facility improvement is recommended to sustain effective technology-enhanced religious learning.